A stepwise crosslinking strategy toward lamellar carbon frameworks with covalently connected alternate layers of porous carbon nanosheets and porous carbon spacers. Issue 73 (24th August 2018) - Huang, Junlong; Lin, Yanhuan; Liu, Shaohong; Liu, Qiantong; Sun, Yiwei; Liang, Yeru; Chen, Yongming; Fu, Ruowen; Wu, Dingcai
Abstract : Lamellar carbon frameworks with covalently connected alternate layers of porous carbon nanosheets and porous carbon spacers were successfully fabricated based on the stepwise crosslinking of self-assembled lamellar block copolymers. Abstract : Lamellar carbon frameworks with covalently connected alternate layers of porous carbon nanosheets (PCNs) and porous carbon spacers (PCSs) were successfully fabricated based on the stepwise crosslinking of self-assembled lamellar block copolymers. The intrinsic porous structure of PCSs can maximize the utilization of well-developed surfaces/interfaces of the PCNs.